Benefits and challenges of distance education in an online foreign language course: German learner perspective - BAŞKAN, NACİ SERHAT (My University, 2023)
Benefits and Challenges of Distance Education in an Online Foreign Language Course: German Learner Perspective Normal 0 21 false false false TR JA X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:\"Normal Tablo\"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:\"; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:8.0pt; mso-para-margin-left:0cm; line-height:107%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:\"Calibri\",sans-serif; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:\"Times New Roman\"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US;} The COVID-19 pandemic ignited discussions about the potential of distance education as a viable alternative to traditional in-person instruction, leading to an expansion in related research. Thanks to digitalization and the proliferation of online tools, delivering educational content has been revolutionized, affording unprecedented ways of learning. This modern approach, which can lead to a paradigm shift, allows learners to access their education from virtually anywhere, paving the way for a flexible and personalized learning environment that is adaptable to their unique schedules and requirements for the differentiated instruction. The primary focus of this study is to scrutinize and appraise the efficacy of synchronous online German language instruction. This evaluation encompasses the quality of teaching, the level of interaction within the online environment, and the usage of Web 2.0 tools, all from the learners’ standpoint. This study aims to explore the experiences and beliefs of learners from different academic fields who enrolled in a German language teaching course at a state university after the post pandemic period. The course was conducted via distance education for one semester in the 2021-2022 academic year. The course content was developed by considering the content development models in distance education. The data collection instruments of the study were an open-ended questionnaire and a semi-structured interview form. The design of the study is based on action research. The collected data were analysed with the help of MaxQDA 2022 qualitative data analysis software. The findings revealed three predominant themes, all from the learners’ perspective: the structure-based issues in distance education, the effectiveness of interaction in distance education, and the thoughts on Web 2.0 tools. These themes provide a comprehensive overview of the current landscape and potential future direction of language learning via distance education. Keywords: distance education, foreign language teaching, web 2.0 tools, online education, learner experience
Keywords: Sosyal ve Beşeri Bilimler; Eğitim; Yabancı Diller Eğitimi; Social Sciences and Humanities; Education; Education in Foreign Languages; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; EĞİTİM, BİLİMSEL DİSİPLİNLER; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; EDUCATION, SCIENTIFIC DISCIPLINES; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities